The epistemological dimension of the concept of problem in the Vygotsky´s work: Implications for science teaching - Simoni Tormöhlen Gehlen; Demétrio Delizoicov (Investigações em Ensino de Ciências, 2012)
Some studies in sience teaching have attributed various meanings to the word problem, and has relied increasingly on the ideas of Vygotsky to set new educational perspectives. It is investigated the role and concept of problem in the Vygotsky’s work and his contributions to the teaching and learning process in science. So, it was carried out a study of major Vygotsky’s works used in sience teaching in Brazil, following the Discourse Textual Analysis. It is noteworthy that the notion of problem in Vygotsky's work is linked to the humanization process, and an epistemological dimension, is related to the object of knowledge. That is, the problem assumes a role in the genesis of creation and appropriation of signs, as well as is the mediator in the relationship between subject and object of knowledge. That prospect poses new questions relating to curriculum and program of science teaching, since it is necessary to consider criteria that define issues to be considered in school curricula.